VD_FINDINFO HC / 2016 / 635 vom 3. Mai 2016 - VD Tribunal cantonal (2016)
DROIT D'ÊTRE ENTENDU, DROIT À LA PREUVE, TÉMOIN, APPRÉCIATION DES PREUVES | 29 al. 2 Cst., 152 al. 1 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH)